Pengaruh Penggunaan Media Sosial terhadap Pola Interaksi Sosial Remaja Perkotaan - Nurcholis Sunuyeko; Sari, Ike Dian Puspita (Universitas Insan Budi Utomo, 2024)
This study explores the shift in social interaction patterns among urban adolescents in Surabaya due to the massive penetration and domination of social media use. Employing a qualitative approach with an exploratory case study design, primary data collection was conducted through semi-structured in-depth interviews and non-participant observation involving 15 adolescents aged 15 to 18 years. The data were then analyzed using thematic analysis techniques. The results reveal four main findings. First, the disruption of the communal essence in the local tradition of